Comparing the impact of the Sport Education model on student motivation in Kuwaiti and American students - Albaloul, Omar; Kulinna, Pamela Hodges; van der Mars, Hans (Frontiers in Psychology, 2024)
Background Sport Education (SE) stands as the most researched pedagogical model in physical education. While researchers have consistently underscored its capacity to improve student motivation in physical education, a gap remains concerning its implications in Arab nations. Moreover, no studies have been identified comparing the outcomes of SE between the U.S., where the model originated, and other countries. Purpose This study was conducted to (1) determine the impact of SE on Kuwaiti students' motivation, (2) determine any differential effects of SE on Kuwaiti and American students' motivation, and (3) explore students' perceptions of SE in both countries. Methods A replicated mixed methods quasi-experimental pre-test and post-test design was used. Participants were 33 secondary school students (nine girls and 24 boys; ages 11–12) from two classes in southwestern US, and 37 secondary school students (12 girls and 25 boys; ages 10–11) from two classes in Kuwait. Both sets of classes across the two countries were instructed by the same teacher who was trained in teaching SE. Student interest/enjoyment, perceived competence, effort/importance, and pressure/tension were measured using the Intrinsic Motivation Inventory instrument (IMI). Student perceptions of SE were assessed using a group Semi-structured interview. Quantitative data were analyzed using repeated measures and mixed ANOVAs followed by t-tests. Qualitative data were analyzed using a thematic analysis technique. Results Kuwaiti students' perceived interest/enjoyment, perceived competence, effort/importance, and pressure/tension scores significantly improved in the group that taught using SE only. Comparing the impact of the SE on students' motivation between the two countries showed no significant differences. The interview data reflected further support for the IMI results. Conclusion SE can be effective in increasing Kuwaiti students' motivation in physical education. This motivating effect of SE was observed consistently across both Kuwaiti and American students.